Peningkatan Kemampuan Motorik Kasar Melalui Permainan Interaktif Di TK Thalabul Ilmi - Arga, Arga; Fitri, Riskal (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2025)
This research aims to improve gross motor skills of kindergarten students through the application of interactive games at TK Thalabul Ilmi. This study uses the classroom action research (CAR) method conducted in two cycles. Each cycle consists of planning, implementation, observation, and reflection. The research subjects were 16 kindergarten students, and data were collected through gross motor skill tests using three assessment aspects: gross motor skills, body coordination, and balance. The results showed a significant improvement in student learning outcomes. In the pre-cycle, only 12.5% of students achieved the "Developing Very Well" criteria, while in Cycle I, the number increased to 56.25%. In Cycle II, 87.5% of students achieved the "Developing Very Well" criteria. The application of interactive games is effective in improving gross motor skills of kindergarten students.